PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI KEWIRAUSAHAAN BERBASIS GENDER SEBAGAI IMPLEMENTASI DESA RAMAH PEREMPUAN DAN PEDULI ANAK - Adi Soeprapto; Susilastuti Dwi Nugrahajati; Suharsono (Dharma: Jurnal Pengabdian Masyarakat, 2026)
Women in villages are often marginalized in terms of access to economic resources, thus limiting their potential to contribute to the village economy. This condition is because the Government and Village Community Institutions do not yet have an optimal strategy for women's economic empowerment. Furthermore, there is still a lack of adequate capacity within the community, especially among women, to develop the family economy. Therefore, this Community Service is aimed at increasing the capacity of village officials and the BPKal in Sendangarum Village in compiling village economic development governance that is socially just through the integration of a gender-based entrepreneurial perspective and strengthening the entrepreneurial capacity of women members of the Women Farmers Group as a form of implementation of the Women-Friendly and Child-Caring Village Policy. The approach used to increase women's role in the economy is through gender-based entrepreneurship, which focuses on providing equal opportunities and utilizing women's potential in the local context. The method implemented is the Participatory Learning and Action (PLA) approach with activities such as workshops, training, mentoring, and facilitation of production equipment and product packaging. The workshop was conducted to improve the capacity of Village Government governance and policies, Entrepreneurship training, and the manufacture of processed agricultural products in the form of fried onions, as well as facilitation of production equipment and product packaging, were conducted to improve the capacity of women entrepreneurs targeting the Women Farmers Group. The results obtained were the knowledge of gender-perspective economic development governance among village officials and BPKal in Sendangarum Village as a basis for the preparation of Village Development Policies and increased women's entrepreneurial capacity, as well as the capacity to manage fried onion business products in the Women Farmers Group.